Crocus heilbronniorum, a new Turkish species of Series Lyciotauri (Iridaceae) - Erol, Osman; Harpke, Doerte; Çi̇ftçi̇ Almila (Phytotaxa, 2017)
Crocus heilbronniorum is described as a new species from Fethiye, Muğla province (SW Turkey). Diagnostic morphological characters, a full description and detailed illustrations are provided based on the type specimen and wild specimens. Morphologically, C. heilbronniorum is close to Crocus atrospermus, but the newly described species differs by its indistinct corm tunic neck, the presence of teeth on rings, basal leaf number and narrower leaves, star-like flowers, longer filaments, almost half length shorter anthers, and style always longer than stamens. Furthermore, Crocus heilbronniorum possesses a different chromosome number (2n = 2x = 12) with regard to C. atrospermus (2n = 10). In order to clarify the phylogenetic position of this species within Series Lyciotauri, data on ITS region sequences are also reported.